Prospects and challenges: Enhancing online appointment system in e-services in Azerbaijan - Mammadova, Narmin; Isayeva, Nigar; Guluzada, Zulaya (ADA University, 2023)
In a constantly changing and developing 21st century, digitalization has become one of the key directions of innovations. Any industry - public or private - is expected to be gradually transferred into digital in order to be assessed as truly “modern”. Considering this reality in mind, this study focused on bringing attention to the online service management system in Azerbaijan, in the face of “ASAN” online appointment system model. This model, obviously, possesses its own advantages and disadvantages, as well as benefits and challenges that [naturally] occur due to internal and external reasons discussed throughout the paper. With a purpose of avoiding subjectivity, having a comprehensive understanding and revealing the big picture, study included comparison with foreign countries, face-to-face interviews with experts from ASAN service and surveys from citizens. Research consisted of five chapters, where each preceding chapter leads to the beginning of another. After introducing the topic, methodology was defined, supported by interviews with the experts in the field and survey as primary data. Policy problems together with its causes allowed to “get to know” the main subject closer. Later, possible solutions against problems were suggested, that were consequently evaluated. It is believed that this study will be a useful scope of information that would benefit both ASAN service and other institutions that aim to transfer their services into digital.
Keywords: Electronic public records -- Azerbaijan; Public services -- Automation; Comparative government -- Case studies; Public and International Affairs